2007
DOI: 10.1097/opx.0b013e318157c6dc
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity with Spherical and Toric Soft Contact Lenses in Low- to Moderate-Astigmatic Eyes

Abstract: Both low- and moderate-astigmatic eyes showed improvements in acuity with toric contact lenses. Lens brand had a measurable effect on acuity for toric contact lenses. Further investigation of aberrations induced by contact lens design is warranted to explain the observed differences in visual performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 13 publications
8
53
0
3
Order By: Relevance
“…The data also suggested some articles using RM-ANOVA did not explicitly test for sphericity using Mauchly's test 18,19 or subsequently correct for this problem using either the Greenhouse and Geisser 20 or Huynh and Feld 21 adjustments. 22,23 The Greenhouse and Geisser adjustment estimates a value of 'epsilon' (e) in order to correct the degrees of freedom of the 'F' distribution, thus enabling a more accurate p value when the sphericity assumption is violated. The Huynh and Feld adjustment is similar but is regarded as more liberal than Greenhouse and Geisser.…”
Section: Resultsmentioning
confidence: 99%
“…The data also suggested some articles using RM-ANOVA did not explicitly test for sphericity using Mauchly's test 18,19 or subsequently correct for this problem using either the Greenhouse and Geisser 20 or Huynh and Feld 21 adjustments. 22,23 The Greenhouse and Geisser adjustment estimates a value of 'epsilon' (e) in order to correct the degrees of freedom of the 'F' distribution, thus enabling a more accurate p value when the sphericity assumption is violated. The Huynh and Feld adjustment is similar but is regarded as more liberal than Greenhouse and Geisser.…”
Section: Resultsmentioning
confidence: 99%
“…Richdale et al [8] compared the visual acuity of subjects with refractive cylinder between 0.75 and 2.00 D in four different Table 2 Plot of mean (±SD) contrast sensitivity at various spatial frequencies with spectacles (baseline), spherical contact lenses and toric contact lenses.…”
Section: Discussionmentioning
confidence: 99%
“…Richdale et al [8] compared the visual acuity and wavefront aberrations in patients fit with spherical, aspheric and toric soft contact lenses and found that the latter yielded the best results. However, subjects had moderate cylindrical power that ranged between 0.75 and 2.00 DC.…”
Section: Introductionmentioning
confidence: 99%
“…Richdale ve ark. 13 Düşük (≤1,00 D) ve orta derecede (≤1,25-2,00D) astigmatizması olan 15 miyopik hastada yumuşak sferik ve torik lens uygulanması sonrasında görme keskinliklerini karşılaştırmışlardır. AcuvueAdvance (Vistakon), Biomedics55 (CooperVision), Frequency55 (CooperVision) ve SofLens66 (Bausch&Lomb) gibi 4 farklı markanın karşılaştırıldığı bu çalışmada torik lensler ile sferik eşdeğerlerine göre daha iyi görme düzeyi elde edilmiş.…”
Section: Discussionunclassified